Analysis of JIANGBA•NANJIE ZHASANG Medical Ethics Thought - ZHAXI DUOJIE; SANGDUO HUAQIAN (Yixue yu zhexue)
JIANGBA•NANJIE ZHASANG, a Tibetan physician in the Ming Dynasty and founder of the northern Tibetan medical school, criticized eight kinds of unethical practices of physicians in his book The Mind of a Doctor. He emphasized the equal importance of medical skills and ethics, aligning his views with the four principles of modern medical ethics: beneficence, non-maleficence, respect and justice. His ethical concepts provided valuable guidance for contemporary medical ethics education and practice. His ideas stressed the balance between morality and technique, integration of theory and practice, cultivation of humility and empathy, adherence to ethical principles, prioritization of patient welfare, continuous learning and self-reflection, and enhancement of doctor-patient communication. These thoughts provided a moral foundation for fostering harmonious doctor-patient relationship and improving medical service quality, serving as a significant reference for the development of modern medical ethics.